Reconstruction of evolving nanostructures in ultrathin films with X-ray waveguide fluorescence holography - Zhang Jiang (Nature Portfolio, 2020)
The authors introduce X-ray waveguide fluorescence holography based on the waveguiding properties of thin films. Combined with model-independent reconstruction algorithms, they show that the method can be used for real-time nanostructure kinetic studies.